2005
DOI: 10.1210/en.2005-0050
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of an Iodothyronine 5′-Deiodinase in Gilthead Seabream (Sparus auratus) that Is Inhibited by Dithiothreitol

Abstract: Iodothyronine deiodinases catalyze the conversion of the thyroid prohormone T(4) to T(3) by outer ring deiodination (ORD) of the iodothyronine molecule. The catalytic cycle of deiodinases is considered to be critically dependent on a reducing thiol cosubstrate that regenerates the selenoenzyme to its native state. The endogenous cosubstrate has still not been firmly identified; in studies in vitro the sulfhydryl reagent dithiothreitol (DTT) is commonly used to activate ORD. We now have characterized an ORD act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 49 publications
0
25
2
Order By: Relevance
“…Two deiodinases (D1 and D2) can catalyze the essential step (Orozco and Valverde, 2005). The deiodinase genes show a pattern of tissuespecific expression of fish species, such as in seabream (Klaren et al, 2005), in walleye (Picard-Aitken et al, 2007). In the present study, high-level expression of the d1 mRNA was not detected in the brains of rare minnow.…”
Section: Discussioncontrasting
confidence: 54%
“…Two deiodinases (D1 and D2) can catalyze the essential step (Orozco and Valverde, 2005). The deiodinase genes show a pattern of tissuespecific expression of fish species, such as in seabream (Klaren et al, 2005), in walleye (Picard-Aitken et al, 2007). In the present study, high-level expression of the d1 mRNA was not detected in the brains of rare minnow.…”
Section: Discussioncontrasting
confidence: 54%
“…Although no endogenous co-substrate has been identified, dithiothreitol (DTT) is commonly used to activate the enzymes in vitro. Both gilthead seabream kidney (Klaren et al 2005) and killifish gill (Orozco et al 2000) D1s have been shown to be inhibited by DTT. This kinetic characteristic seems be tissue specific.…”
Section: Biochemical Propertiesmentioning
confidence: 99%
“…ORD activities were assayed following the method described by Klaren et al (2005). We used reverse T 3 (rT 3 , 3,3 0 ,5 0 -triiodothyronine) and T 4 as the preferred substrates for 5 0 -deiodinases (Mol et al 1998).…”
Section: Ord Activitiesmentioning
confidence: 99%